(1200) education, educational planning in the developing countries - mandi, peter (the institute of national planning, 2018)
the economics of education achieved the status of science as a result of the realization that the quality of manpower had grown into an important economic factor. as the quality of manpower is determined by the vocational skill and knowledge, the culture and general education applicable in work.